Assessment of knowledge, attitudes, and practices regarding personal protective equipment use among employees in a thermal power station of central India: a cross-sectional study - Shingnad, Saurabh; Wadhva, Sarita; Rathod, Pragati; Narlawar, Uday; Padyal, Pratik (International Journal Of Community Medicine And Public Health, 2024)
Background: Personal protective equipment (PPE) is crucial for ensuring work safety in high-risk environments, such as thermal power stations. Proper use of PPE reduces the risk of occupational hazards. This study aims to assess the knowledge, attitudes, and practices (KAP) regarding PPE use among thermal power station employees. Methods: A cross-sectional study was conducted among 250 employees of a thermal power station. Data was collected using a structured questionnaire designed to evaluate KAP towards PPE use. Descriptive statistics, including frequency and percentages, were used for data analysis to summarize participants’ responses. Results: The majority 96.8% knows about the types of PPE used. The 82% had a positive attitude towards its use while 60.8% study subjects reported that they consistently wear all relevant PPE at their workplace. Conclusions: The employees had adequate knowledge and attitudes towards PPE, however actual compliance with its use remains suboptimal. Interventions focused on reinforcing PPE usage practices are needed.